The endothelial dysfunction factors in diabetes mellitus 2 type - Chernobryvtsev, O. P. (Journal of Education, Health and Sport, 2019)
Aim: to investigate the association of EDF factors: endothelin 1 (ET1), endothelial NO-synthase (eNOS), nitric oxide (NO), tumor necrosis factor (TNFα), and diene conjugates (DC) with severity of type 2 diabetes. Material and methods. Data were used for 152 hospital patients with type 2 diabetes at the age from 34 to 80 years (53.9±8.4 years). Women were 95 (62.5%), men – 57 (37.5%). According to the degree of severity of patients was divided into three groups: 1st (37.5% of patients) – the average stage in the compensation stage (HbA1s 7-9%), 2nd (41.4%) – the average stage in the stage of decompensation (HbA1s more than 9%), 3rd (21,1%) – a severe degree in the stage of decompensation. The control group included 95 practically healthy individuals. The plasma levels of the blood were determined by the enzyme-linked method: ЕТ1 (Biomedica Immunoassays, Austria), eNOS (BCM Diagnostics, USA) і TNFα (Bender Medsystems, Austria). The level of blood NO and DC were determined biochemically (spectrophotometer Specord, Germany). Statistica 10 (StatSoft, Inc., USA) was used to statistically process the data obtained. Results. Levels of EDF factors depended on the severity of DM 2 type. Thus, the level of ETI in patients exceeded control in 3.7-4.7 times (p<0.001) with the maximum values in the 2nd and 3rd groups; also increased blood levels of NO (1.4-1.5 times; p<0.001). The highest increase was observed in TNFα levels (4.2-6.5 times; p<0.001) and DC (2.3-2.7 times; p<0.001). The blood content of eNOS in the patients’ groups was lower when compared with control (1.3-1.9 times; p<0.001). Conclusion. Factors of EDF are closely linked with clinical and laboratory indicators of severity of DM 2 type, which highlights them in the pathogenesis of the disease.